"That's who I am: A fat person in a thin body": Weight loss, negative self‐evaluation, and mitigating strategies following weight loss surgery. Issue 3 (25th July 2014) - Alegría, Christine Aramburu; Larsen, Barbara
Abstract Objective To explore negative self‐evaluation following weight loss surgery (WLS). Methods In‐depth interviews were conducted with 11 women who had WLS. Thematic analysis was conducted through an iterative process, allowing categories and themes to emerge. To ensure rigor, two coders analyzed the data. Data were collected until thematic saturation was achieved. Results All participants reported health as the motivation for WLS. Overall sentiment regarding WLS was positive. However, negative self‐evaluation was reported and includes the following: (a) body‐image distortion; (b) body‐image dissatisfaction, including excessive skin; and (c) perceived stigma. Mitigating strategies include the following: (a) utilizing markers of progress to increase assimilation of a new identity as a thinner person, and (b) reflecting on the former self as a time of decreased quality of life. Implications for practice Nurse practitioners and other clinicians treat and counsel patients on obesity and obesity‐related morbidity, and may need to discuss WLS with patients who are either contemplating it or have already undergone it. The findings from the present study can provide clinicians insight into the possible psychological effects of WLS‐associated weight loss. Bringing possible negative self‐evaluative effects into open discussion can help optimize patient care and healthcare results.